Emotional distress and quality of life in teachers during the pandemic - Vlad, Valentin; Sandu, Mihaela Luminița (Eximia, 2023)
The advent of the COVID-19 pandemic precipitated an unparalleled public health exigency globally. The enforced cessation of operations within educational edifices necessitated an expeditious shift from traditional pedagogy to a virtual educational paradigm. The initial and most palpable repercussion of the Coronavirus pandemic was observed in the alteration of human lifestyles. It drastically redefined interpersonal dynamics. Concurrently, there was a discernible transformation in individual attitudes towards self and others. Nevertheless, the exigencies of social isolation were found to be particularly arduous for individuals in solitude. Solitary inhabitants became acutely aware of their isolation, bereft of familial, social, and professional interactions. The imminent peril of the contagion engendered heightened vigilance towards personal health, compelling adherence to stringent regulations, notwithstanding the inherent sociability of humans. The intrinsic human yearning for social interaction, a component of self-actualization, was temporarily obviated. Concomitantly, the deleterious ramifications of social isolation and solitude began to surface. The eradication of customary leisure activities precipitated a void, punctuated by a collective inability to utilize time constructively. The impetus for selecting this subject matter was its contemporaneity and the desire to delve deeper into the tribulations engendered by the pandemic. Experiencing these tribulations from a student’s perspective fostered a curiosity about their impact on educators. This discourse aims to elucidate the perturbations in quality of life and emotional distress, as well as the organizational stress effects during the pandemic epoch. Given the abrupt migration to online pedagogy necessitated by the pandemic, the study centers on pre-university educators, employing two digital questionnaires for data collection. The primary goal of this inquiry is to ascertain the correlation between emotional distress and various facets of life quality among pre-university pedagogues.